Characterization of weathered rock for excavation work / Mohd Akmal Arif Hj Mohd Zafri - Hj Mohd Zafri, Mohd Akmal Arif (2015)
The engineering properties of weathered rock are very critical especially related to quantifying whether it is a rock, soft rock or hard material. The vast definitions of weathered rock always resulted to disputes between the practitioners, client and contractor in interpreting the rock state. Issues of excavation technology and rate of payment will arise. Thus, lead to wrongly selection of excavation tool and unproductive excavation, time consuming and loss of claim. This research shall explain the characterization of weathered granite and sandstone in Malaysia and method of engineering classification for excavation purposes. Rock cutting technology attached on excavation works on site also being discussed in aspects of excavability index. The field observations on site were also carried out to get the genuine data of rock cutting techniques applied on site for various grade of weathered rock. A series of laboratory testing also been carried out to determine the significant properties of weathered granite and sandstone, strength, texture, cyclic load and also to evaluate the excavation efficiencies of the weathered rocks. Cyclic load test is a simulation test of the hydraulic breaker used on site. Ripping is known as one of the excavation method which used to excavate rock. This method is suitable for weak rock which is very hard to excavate by the normal excavator nevertheless feeble to blast. From this study, it shows that the excavation efficiency had direct proportional to the increasing of weathering grade. In addition, it shows that an accurate selection and combination of cutting tool can efficiently excavate the volume of weathered granite and sandstone rock at optimum cost.